Mathematical modeling of thermal modes of thermosyphons in operation with characteristic heat loads of aircraft equipment batteries; Russian Aeronautics; Vol. 60, iss. 2 - Krasnoshlykov A. S. Aleksandr Sergeevich (2017, 2017)
Title screen